Changes in H2A.Z occupancy and DNA methylation during B-cell lymphomagenesis - Conerly, Melissa L.; Teves, Sheila S.; Diolaiti, Daniel; Ulrich, Michelle; Eisenman, Robert N.; Henikoff, Steven

(untitled) (Genome Research, 2010)
The histone variant H2A.Z has been implicated in the regulation of gene expression, and in plants antagonizes DNA methylation. Here, we ask whether a similar relationship exists in mammals, using a mouse B-cell lymphoma model, where chromatin states can be monitored during tumorigenesis. Using native chromatin immunoprecipitation with microarray hybridization (ChIP-chip), we found a progressive depletion of H2A.Z around transcriptional start sites (TSSs) during MYC-induced transformation of pre-B cells and, subsequently, during lymphomagenesis. In addition, we found that H2A.Z and DNA methylation are generally anticorrelated around TSSs in both wild-type and MYC-transformed cells, as expected for the opposite effects of these chromatin features on promoter competence. Depletion of H2A.Z over TSSs both in cells that are induced to proliferate and in cells that are developing into a tumor suggests that progressive loss of H2A.Z during tumorigenesis results from the advancing disease state. These changes were accompanied by increases in chromatin salt solubility. Surprisingly, ∼30% of all genes showed a redistribution of H2A.Z from around TSSs to bodies of active genes during the transition from MYC-transformed to tumor cells, with DNA methylation lost from gene bodies where H2A.Z levels increased. No such redistributions were observed during MYC-induced transformation of wild-type pre-B cells. The documented role of H2A.Z in regulating transcription suggests that 30% of genes have the potential to be aberrantly expressed during tumorigenesis. Our results imply that antagonism between H2A.Z deposition and DNA methylation is a conserved feature of eukaryotic genes, and that transcription-coupled H2A.Z changes may play a role in cancer initiation and progression.